Need Analysis of Virtual Laboratories For Science Education In Jambi, Indonesia - Fahmi Rohim (Jurnal Sains Sosio Humaniora, 2020)
The needs of technological advancement which is infused into education system are more and more inviting thorough researches since digital environment influences educational settings. In specific, virtual laboratories as the digital environment is now not used only in engineering and computer science fields but also in educational field in general. Digitalized teaching aids, web-based learning, e-learning etc. are such possible prospective fields that need virtual labs in them. In regard to that, this study is initiated to conduct a need analysis of virtual labs for Jambi province context through library research. This study employs documentary analysis techniques to assimilate reliable information regarding virtual labs from the related literatures. Purposively, this study selects online journals that are correlated to virtual labs and analysed the variables, methods, and results of study. This study finds that studies done yield few shortcomings of virtual labs usages to only the lost opportunity of students to involve their senses during the use of virtual labs. However, in general virtual labs usages contribute benefits to science education such as: a) Virtual labs assist students to link between theoretical and scientific concepts to practical laboratory techniques and skills; b) Virtual labs provide simulations that make students more engaged in learning scientific phenomena; c) Although some important opportunities of learning experiences are not provided by virtual labs such as sensory involvement in learning, most virtual labs are developed to fulfil the characteristics of teaching aids; d) Virtual labs abbreviate the preparation steps of practicum activities, hence they make class-time used effectively; and e) Virtual labs allow students to repeat experiment for multiple times. In addition, virtual labs usages also bring prospects to some important aspects of educational field namely financial resources, academic advancement, technological computer simulation improvement, and cultural aspects. This study suggests the Jambi Education Board to recommend virtual labs usages at schools to equip science education as supplemental and supporting teaching aids.